Referral Patterns for Emergency Psychiatric Evaluations and Effect of School Mental Health Services in New York City, 2018. (25th April 2022) - St. Pierre‐Hetz, Ryan; Silver, Ellen; Chokroverty, Linda; Collins, Kari; Khine, Hnin
ABSTRACT: BACKGROUND: Pediatric mental health issues are increasing while access to care is decreasing. This is reflected in a growing number of patients seeking emergency psychiatric evaluations (EPEs) in the emergency department (ED). METHODS: This was a retrospective review of patients seeking EPE in the ED of a children's hospital between September and December 2018, which compares patients referred from the community versus those from schools as well as patients from schools with and without school‐based mental health services (SMH). RESULTS: A total of 546 EPEs were analyzed, with 187 (34%) referred from schools. School referrals were younger, had a shorter length of stay and lower admission rates. When comparing those from schools with SMH, those referred from schools without SMH were younger and less acutely ill. CONCLUSIONS: Higher acuity children from schools with SMH suggest that SMH staff managed less severe situations on site. The role of SMH as a triaging tool and provider of mental health services should be studied as they may reduce the burden on EDs for EPEs.